Cultural Identity and Individualism-Collectivism Among Students at a University in Southern Peru - Hualla Ortega, Henrry Alexis (2025)
The objective of this research was to analyze the relationship between cultural identity and individualistic-collectivist orientation in a sample of 277 university students enrolled at a university located in southern Peru. Participant selection was performed using convenience probability sampling. The study follows a quantitative approach, with a basic purpose and a relational level of knowledge. The methodological design is non-experimental, descriptive-correlational, and cross-sectional. Data collection was performed using a survey technique using two instruments: the Individualism-Collectivism Scale developed by Soler and Díaz (2017) and the Cultural Identity Test developed by Vicuña Peri (1987), both adapted to the local context. The results show that 39.35% of participants presented a low level of cultural identity, while 36.82% reflected a high level of individualism. Likewise, a significant relationship was found between the variables studied, with a 95% confidence level and a 5% margin of error.